ANALISIS PENGARUH STRUKTUR DAN MEKANISME GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP MANAJEMEN LABA - Putri, Intania Destiani; Sofian, Syuhada (Faculty of Economics and Business Diponegoro University, 2013)
Manufacture firms are in the stage of large enterprise companies that support the economy of the country. In the scope of manufacture emerged many new players that enhance competition by both new players and old players, so there is a big possibility to do earnings management. This study aimed to examine the effect of Good Corporate Governane structure and mechanism, firm size, and leverage on earnings management. Good Corporate Governance indicators used are institutional ownership, managerial ownership, the proportion of independent commissioners and audit committee.This study uses secondary data, that was financial report of the companies in the manufacturing category listed on the Indonesia Stock Exchange. The sample used 19 companies in the manufacturing category during the period 2007-2011. The analysis method used is OLS regression (Ordinary Least Square) with a significance level of 5%.Based on the results from ordinary least square regression analysis for six independent variables showed that managerial ownership and the audit committe has significant effect on earnings management, but managerial ownership has different direction with the hypothesis.While the institutional ownership, the proportion of independent comissioner, firm size and leverage does not influence earnings management.